ETHICAL COMPLIANCE OF LOCAL TELEVISION JOURNALISTS (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Based on the preliminary survey conducted by researchers on a number of local Malang television, this study shows that the journalist's ethical compliance factor only acts as a precondition towards the professionalism of television journalists, because there are three other important components, namely authority, supervision and service. If these three components are "activated", they will become an institutionalized system. So professionalism is a system of relations between authority, supervision, and institutionalized services. Authority is derived from competence, work activities, and organization. This article discusses the extent to which journalists adhere to writing a report. The emphasis here is given to the aspect of the method of examining the objectivity of journalists in selecting news. In reality, the mass media has been controlled by corporations and because of that obscures the meaning of press freedom which has been the most important jargon in the journalistic world. The relationship between media workers and capital owners is no longer merely a functional relationship, but it has shown the dominance that has become a model in various media institutions. Because both capital owners and media workers have the same goal, namely the survival of the media as a business and political institution framed in the name of the role of the media in the life of democracy.